Synthesis of Symmetrical Biaryls through Palladium-Catalyzed Ligand-Free Homocoupling of Aryliodine(III) Diacetates - Xiong, Qiheng; Fu, Zhengjiang; Li, Zhaojie; Cai, Hu (Synlett, 2015)
An efficient process for the synthesis of symmetrical biaryls from readily available and bench-stable aryliodine(III) diacetates has been developed with high regional selectivity. The process exhibited high selectivities and good functional group tolerance with respect to methyl, bromo, chloro and cyano groups. Mechanistic studies revealed that the transformation involved in situ generation of aryl iodide from heating-promoted degradation of aryliodine(III) diacetate, followed by Ullmann-type homocoupling.
Keywords: biaryls; palladium; homogeneous catalysis; coupling; chemoselectivity